Micro-diaphragm performance analysis for polyimide diaphragm - Hasikin, K.; Soin, N.; Ibrahim, F. (2010)
This paper presents a micro-diaphragm performance analysis for optical sensor for human pulse pressure detection. The effect of diaphragm radius and diaphragm thickness on the static and frequency responses were investigated. It can be concluded that the polyimide micro-diaphragm with a radius of 90Î¼m and thickness of 4Î¼m has achieved the optimum performance in term of the sensitivity, flexural rigidity and resonance frequency. Â© 2010 IEEE.